2020
DOI: 10.18806/tesl.v37i2.1339
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Written Corrective Feedback among Graduate Students: The Effects of Feedback Timing

Abstract: Dynamic written corrective feedback (DWCF) is a pedagogical approach that offer meaningful, manageable, constant, and timely corrective feedback on student writing (Hartshorn et al., 2010). It emphasizes indirect and comprehensive writte error correction on short, daily writing assignments. Numerous studies have demonstrated that its use can lead to fewer language errors among undergraduate and pre-matriculated college writers (see Kurzer, 2018). However, the benefits of DWCF among second language (L2) graduat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This finding corresponded to the previous studies in which the students with dynamic WCF exhibited a decrease in MLT, C/T, and CN/T from pre-to post-tests (Eckstein & Bell, 2021;Hartshorn et al, 2010). One explanation outlined by previous research is that students' attempts to improve accuracy may hinder the development of their syntactic complexity (Eckstein et al, 2020;Hartshorn et al, 2010). In Eckstein et al 's (2020) study, it was argued that L2 writers might employ linguistically simplified structures to improve their linguistic accuracy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding corresponded to the previous studies in which the students with dynamic WCF exhibited a decrease in MLT, C/T, and CN/T from pre-to post-tests (Eckstein & Bell, 2021;Hartshorn et al, 2010). One explanation outlined by previous research is that students' attempts to improve accuracy may hinder the development of their syntactic complexity (Eckstein et al, 2020;Hartshorn et al, 2010). In Eckstein et al 's (2020) study, it was argued that L2 writers might employ linguistically simplified structures to improve their linguistic accuracy.…”
Section: Discussionsupporting
confidence: 86%
“…Limited studies in WCF research examined whether and how the provision of WCF influences students' syntactic complexity in writing (Eckstein & Bell, 2021;Eckstein et al, 2020;Hartshorn & Evans, 2015;Van Beuningen et al, 2012;Xu & Zhang, 2021) (Table 1). Generally, findings from such studies have remained inconclusive: some studies (e.g., Van Beuningen et al, 2012) found that WCF did not cause students to produce structures that were linguistically simplified, whereas others (e.g., Hartshorn & Evans, 2015) stressed an adverse effect on writing complexity.…”
Section: Written Corrective Feedback and Its Effects On Syntactic Com...mentioning
confidence: 99%
“…They also expressed some other issues such as time constraints and the amount of workload they had misaligned with their beliefs towards WCF practice. However, the study by Eckstein et al (2020) was conducted on the effects of dynamic WCF and feedback timing on graduate students. The researchers investigated how the given feedback impacts grammatical accuracy and lexical complexity.…”
Section: Corrective Feedback: From 2016 To 2022mentioning
confidence: 99%
“…A final article-the only research study investigating graduate students specifically-reported on a study that contrasted the timing of DWCF (spread throughout the term or lumped together at the end of the term) with 22 multilingual graduate students, finding gains in fluency and complexity in the group that received regular feedback, but no statistically significant improvements regarding grammatical accuracy in either group (Eckstein et al, 2020). These results may identify a ceiling level upon which DWCF may no longer be effective at supporting increased grammatical accuracy in student writing, although it may still be helpful at influencing student writing in other manners.…”
Section: Research Articlementioning
confidence: 99%